An analysis of economic benefits from adoption of drought tolerant soybean (Glycine max) in Madhya Pradesh - J, RAGHAVENDRA K; SURESH, A (The Indian Journal of Agricultural Sciences, 2020)
The research conducted to estimate the potential economic benefit from adoption of drought tolerant soybean (Glycine max (L.) Merr.) variety NRC-7 in Indore district of Madhya Pradesh, where majority of area is under rainfed system. In this study, the potential economic benefit in terms of economic surplus and risk reduction was estimated for NRC-7 and alternative varieties, JS-93-05 and JS 95-60. NRC-7 requires less cost of cultivation compared to other two varieties, and withstands stress condition. In normal condition, the economic surplus for NRC-7 was ₹ 686 million per year, and that of, JS-93-05 and JS 95-60 is about ₹ 3161 million, ₹ 6291 million, respectively. For NRC-7, the risk reduction benefit was to the level of ₹ 547 million, which accounted for about 83.8% of total benefits for that variety. On per ha basis, NRC 7 performs well over the other two varieties in reducing the fluctuation in income of farmers. So there is a need to develop and increase the awareness of abiotic stress tolerant varieties to cope up with the income fluctuation due to weather risks.